Behavioural changes in transport and future repercussions of the COVID-19 outbreak in Spain. (September 2021) - Echaniz, Eneko; Rodríguez, Andrés; Cordera, Rubén; Benavente, Juan; Alonso, Borja; Sañudo, Roberto
Abstract: COVID-19 (Coronavirus disease 2019) brought about a huge change in the behaviour and mobility of citizens in all parts of the world. This change was mainly a consequence of the strong measures of isolation and social distancing taken by the different governments in most countries through the world. The specific measures adopted in each country, in combination with the particular characteristics of the spread of the virus, generated differentiated, although similar, behavioural changes. This article presents the analysis of a survey carried out in Spain in March 2020, where citizens were asked about their mobility preferences before, during and after the lockdown due to the virus. In turn, questions were asked about the preferred modes of transport in each of the situations and the perception of safety on public transport in their current conditions. The mobility questions were differentiated between commuting to work or studies, shopping and leisure. The results show that public transport was the most affected transport mode, with a considerable increase in the use of the bicycle and walking trips. At the same time, changes were observed in the behaviour of shopping trips, including a considerable decrease on the use of large supermarkets. Citizens perceived great uncertainty in planning leisure trips, the consequence of which could be that a higher proportion of people not being able to carry out their planned trips. Highlights: A large part of the trips planned by citizens could not be carried out by COVID-19. Public transport was the most affected transport system by the COVID-19 pandemic. COVID-19 affected citizens' shopping behaviour. Modal shifts in transport were different depending on the size of the city. Public transport will need measures to guarantee security against the virus to return to normal conditions.